产业集群竞争优势的决定因素 = Determinants of industrial cluster's competititve advantage - 谷正海 Gu, Zhenghai (2008)
Since the beginning of Chinese reform & opening, there have resulted in a number of Amoeboid industrial cluster in the East Coast Zone of China. The competitive advantage of industrial cluster is neither in its blood, nor exit forever spontaneously. The development of industrial clusters that are oriented in the mature period can take fully the competitive advantages.